Development of Learning Modules for Senior High School Semester V Based on the Independent Curriculum - Natasya, Umy; Hutagalung , Surya Masniari (Asian Journal of Applied Education (AJAE), 2024)
This research is about the creation of a learning module for the 5th semester of high school based on the Independent Curriculum with the theme "die Familie (Family)". This research focuses on the creation of printed learning modules. This study uses a qualitative descriptive method through data collection using questionnaires with data sources from the Independent Curriculum, German books and information from the Internet. This development research is a development that uses Richey and Klein's theory. The research model consists of 3 steps, namely: 1) Planning, 2) Making, 3) Evaluation. The result of this research is a printed module in the form of a German language learning module for the theme "die familie (Family)". This learning module has gone through the process of material and design validation and received an assessment from experts of 93.75.